Analysis of the Foreign Trade and Gross Domestic Product Effect on Foreign Direct Investment using Panel Data Regression Estimation - Winda Putri Anggraini (University of Mataram, 2021)
Investment is one of the components that determines a country's economic growth. Sources of investment funds can be seen through two approaches, domestic investment and foreign investment. One of the promising components of foreign investment is Foreign Direct Investment (FDI). FDI is considered more valuable for the country because it is more long-term in nature. This study aims to see the effect of Gross Domestic Product (GDP) and export-import as foreign trade activities on FDI, through estimation with panel data regression model. The data used is data from 20 countries with observation period from 2009 to 2018. With the Random Effect Model as the best model, which the estimators also qualify the BLUE estimator. it can be concluded that partially the GDP variable has no significant effect. Meanwhile, exports have a significant positive effect and imports have a significant negative effect on FDI.